State of the Art Bowel Management for Pediatric Colorectal Problems: Functional Constipation - Elizaveta Bokova; Wendy Jo Svetanoff; John M. Rosen; Marc A. Levitt; Rebecca M. Rentea (MDPI AG, 2023)
Background: Functional constipation (FC) affects up to 32% of the pediatric population, and some of these patients are referred to pediatric surgery units to manage their constipation and/or fecal incontinence. The aim of the current paper is to report the recent updates on the evaluation and management of children with FC as a part of a manuscript series on bowel management in patients with anorectal malformations, Hirschsprung disease, spinal anomalies, and FC. Methods: A literature search was performed using Medline/PubMed, Google Scholar, Cochrane, and EMBASE databases and focusing on the manuscripts published within the last 5-10 years. Results: The first step of management of children with FC is to exclude Hirschsprung disease with a contrast study, examination under anesthesia, anorectal manometry (AMAN). If AMAN shows absent rectoanal inhibitory reflex, a rectal biopsy is performed. Internal sphincter achalasia or high resting pressures indicate botulinum toxin injection. Medical management options include laxatives, rectal enemas, transanal irrigations, and antegrade flushes. Those who fail conservative treatment require further assessment of colonic motility and can be candidates for colonic resection. The type of resection (subtotal colonic resection vs. Deloyer's procedure) can be guided with a balloon expulsion test. Conclusion: Most of the patients with FC referred for surgical evaluation can be managed conservatively. Further studies are required to determine an optimal strategy of surgical resection in children unresponsive to medical treatment.